2008
DOI: 10.1186/1471-2407-8-375
|View full text |Cite
|
Sign up to set email alerts
|

Increased p38-MAPK is responsible for chemotherapy resistance in human gastric cancer cells

Abstract: BackgroundChemoresistance is one of the main obstacles to successful cancer therapy and is frequently associated with Multidrug resistance (MDR). Many different mechanisms have been suggested to explain the development of an MDR phenotype in cancer cells. One of the most studied mechanisms is the overexpression of P-glycoprotein (P-gp), which is a product of the MDR1 gene. Tumor cells often acquire the drug-resistance phenotype due to upregulation of the MDR1 gene. Overexpression of MDR1 gene has often been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 45 publications
3
86
0
Order By: Relevance
“…It has also been reported that NF-κB levels are significantly associated with poor prognosis of gastric cancer (27). Guo et al revealed that the activation of the NF-κB dimer was significantly higher in drug-resistant gastric cancer cell lines than its parental cell lines (28). Therefore, NF-κB is proposed as a specific molecule related to drug resistance and is a potential therapeutic target for the treatment strategy of gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that NF-κB levels are significantly associated with poor prognosis of gastric cancer (27). Guo et al revealed that the activation of the NF-κB dimer was significantly higher in drug-resistant gastric cancer cell lines than its parental cell lines (28). Therefore, NF-κB is proposed as a specific molecule related to drug resistance and is a potential therapeutic target for the treatment strategy of gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the active form of PI3K is related to an increase of Pgp expression (46). Furthermore, several molecular pathways, such as NF-κB, ERK/MAPK, and p38-MAPK, among others, are also associated with the regulation of Pgp expression in cancer cells (47)(48)(49). A recent study showed that the MDR phenotype in K562 cells could be reversed by inhibition of the NF-κB pathway, suggesting a regulation of Pgp through modulation of NF-κB (50).…”
Section: Discussionmentioning
confidence: 99%
“…it can be stimulated by various stresses such as uv and γ irradiation, osmotic stress, heat shock and some chemotherapeutic drugs (19). a recent study (20) found that inhibition of p38 MaPK downregulated a multidrug-resistance i gene, which was believed to be responsible for chemotherapy resistance in gastric cancer cells. However, to date we could not find any report providing insight into the details of the role of p38 MaPK pathway in 5-fu resistance in crc cells.…”
Section: Discussionmentioning
confidence: 99%